If I multiplied these binomials (x - 3) + (4x + 2) what would be the final product?
2 answers:
Answer: 4x^2 - 10x - 6
Step-by-step explanation:
You can use FOIL to do this. First terms, Outer terms, Inner terms, Last terms.
(x - 3)(4x + 2)
First terms: x * 4x = 4x^2
Outer terms: x * 2 = 2x
Inner terms: -3 * 4x = -12x
Last terms: -3 * 2 = -6
Now add these together:
4x^2 + 2x - 12x - 6 = 4x^2 - 10x - 6
Answer:
4x^2 - 10x - 6
Step-by-step explanation:
If you truly want to multiply these binomials, remove the " + " sign and replace it with " * " for multiplication:
(x - 3) (4x + 2) = 4x^2 + 2x - 6 - 12x
Combining like terms, we get 4x^2 - 10x - 6
You might be interested in
Answer:
y = 5; x = 1/5
Step-by-step explanation:
xy = 1 -----> x = 1/y
xy^2 = 5 -----> 1/y * y^2 = 5
y^2 / y = 5
y = 5
5x = 1
x = 1/5
Hope this Helps!
Answer:
20
Step-by-step explanation:
2x - 5 = x + 15
2x - x = 5 + 15
x = 20
The area for the enclosed area is 210
Rectangle A=bh=4 x 3
Triangle A=1/2bh=1/2 x4 x3
The area of the figure
12+6=18